Pengaruh Current Ratio, Return On Assets dan Debt to Equity Ratio Terhadap Harga Saham Pada Perusahaan Sektor Kesehatan yang Terdaftar di BEI Periode 2017-2021 - Fina Adlia; Diah Yudhawatib; Azolla Degita Azis (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine the effect of Current Ratio (CR), Return On Assets (ROA), and Debt to Equity Ratio (DER) on the share price of Health Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. The method of analysis used in this study is to use quantitative methods with Generalized Least Square regression with the Fixed Effect Model (FEM), using secondary data obtained from data published by the Indonesia Stock Exchange and Yahoo Finance as well as other supporting data obtained from IDX Statistics. The results showed that partially (t test) the Return On Assets (ROA) variable had a significant effect on stock prices, the Current Ratio (CR) variable had no effect on stock prices and the Debt to Equity Ratio (DER) variable had no effect on stock prices. Profitability information is considered very important for companies because this information will be a signal for investors and the company's profitability will reflect the company's share price.